2017
DOI: 10.3897/phytokeys.83.12797
|View full text |Cite
|
Sign up to set email alerts
|

Stipa pennata subsp. ceynowae (Poaceae, Pooideae), a new taxon from Central Europe

Abstract: Based on numerical analyses of macromorphological characters, scanning electron microscopy observation of leaves and lemma micromorphology, as well as field observations, Stipa pennata subsp. ceynowae was described here as a new taxon from Poland. It differs from the most similar S. pennata subsp. pennata and S. borysthenica mainly by its longer ligules of vegetative shoots. The affinities of this taxon are discussed and a morphological comparison with related species is provided. Illustrations and images of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…An extreme example is here the complete absence of nucleotide differences between cpDNA of S. pennata subsp. ceynowae and S. borysthenica as well as very small differences reaching 0.009% for S. jagnobica and S. richteriana and 0.012% between S. arabica and S. hohenackeriana , despite of the fact that all of the aforementioned species are morphologically well separated and easily identifiable 3 , 5 , 52 . The comparative analysis of complete cpDNA sequences as super-barcodes in the case of Stipa was much more effective than a traditional barcoding approach.…”
Section: Discussionmentioning
confidence: 95%
“…An extreme example is here the complete absence of nucleotide differences between cpDNA of S. pennata subsp. ceynowae and S. borysthenica as well as very small differences reaching 0.009% for S. jagnobica and S. richteriana and 0.012% between S. arabica and S. hohenackeriana , despite of the fact that all of the aforementioned species are morphologically well separated and easily identifiable 3 , 5 , 52 . The comparative analysis of complete cpDNA sequences as super-barcodes in the case of Stipa was much more effective than a traditional barcoding approach.…”
Section: Discussionmentioning
confidence: 95%
“…) Stipa boryshtenica is a widely distributed taxon ranging from central Europe to central Asia (Tzvelev 1976, Martinovský 1980, Conert 1998, Gonzalo et al 2013 and is here reported for the first time from China. Having the ventral line of hairs at the anthecium at the distance of (1.6-)4.2-6.1(-7.7) mm not reaching the base of awn and almost glabrous to slightly scabrous vegetative leaves, S. boryshtenica is close to S. pennata, however they differ by having callus base narrowly cuneate vs. pyriform, callus (3.4-)3.7-4.2(-4.6) vs. (2.4-)2.8-3.25(-3.75) mm long, upper cauline leaves (22-)36-62(-125) vs. (4-)10-22(-40) mm long respectively (Klichowska & Nobis 2016). These two taxa also differ in the type of habitat in which they grow.…”
Section: Stipa Borysthenica Klokov Ex Prokudinmentioning
confidence: 99%
“…puberula Podpěra & Suza, S. disjuncta Klokov, S. graniticola Klokov, S. pennata subsp. ceynowae Klichowska & M. Nobis [8, 9]. …”
Section: Introductionunclassified